UMTS - Dahlman, E. (IEEE Communications magazine)
The UMTS terrestrial radio access is based on wideband 4.096 Mchip/s DS-CDMA technology. UTRA will be connected to an evolved GSM core network for both circuit and packet services. A merger between ETSI/Europe and ARIB/Japan based on W-CDMA, a GSM core network, and a common frequency allocation according to the ITU Recommendation of 2 GHz makes a global IMT-2000 standard feasible. UTRA based on W-CDMA fully supports the UMTS/IMT-2000 requirements (e.g., support of 384 kb/s for wide-area coverage and 2 Mb/s for local coverage). Furthermore, the air interface has flexible support of mixed services, variable-rate services, and an efficient packet mode. Key W-CDMA features also include improved basic capacity/coverage performance compared to second-generation systems, full support of adaptive antenna arrays, support of hierarchical cell structures with interfrequency handover, and support of asynchronous inter-base-station operation. There have been no constraints due to the strong requirements for backward compatibility with second-generation systems. This has facilitated a high degree of flexibility and a future-proof air interface. Extensive evaluations by means of simulations and field trials have been carried out by a number of companies, and full system tests are ongoing. Consequently, W-CDMA technology can now be regarded as a mature technology, ready to provide the basis for UMTS/IMT-2000